Characterization, antibacterial, anticarbonic anhydrase II isoenzyme, anticancer, electrochemical and computational studies of sulfonic acid hydrazide derivative and its Cu(II) complex - Ozdemir, Ummuhan O.; Aktan, Ebru; Ilbiz, Firdevs; Gunduzalp, Ayla B.; Ozbek, Neslihan; Sari, Musa; Saydam, Sinan (Elsevier Science Sa, 2014)
A new N'-acetyl butane sulfonic acid hydrazide, C4H9-SO2-NH-NH-COCH3 (Absh, an sulfonamide compound), and its Cu(II) complex [Cu(Absh)(2)(CH3COO)(2)], have been synthesized and characterized by elemental analysis, spectrometric methods (H-1-C-13 NMR, FT-IR, LC-MS), thermal analysis, magnetic susceptibility and conductivity measurements. In addition, molecular structure of the ligand, Absh was determined by single crystal X-ray diffraction technique and found that the compound crystallizes in monoclinic, space group P2(1)/c. To gain information about the structure of the ligand and its complex, we have performed computational studies using density functional theory (DFT) for optimized geometries of the compounds. Electrochemical studies showed that, the complex is electrochemically active and has one irreversible reduction and one irreversible oxidation potentials, and the half wave reduction potentials are -1.15 and 0.45 volt respectively, versus ferrocene/ferrocenium internal reference electrode. The antibacterial activities of synthesized compounds were studied against Gram positive bacteria; Staphylococcus aureus ATCC 6538, Bacillus subtilis ATCC 6633, Bacillus cereus NRRL-B-3711, Enterococcus faecalis ATCC 29212 and Gram negative bacteria; Escherichia coli ATCC 11230, Pseudomonas aeruginosa ATCC 15442, Klebsiella pneumonia ATCC 70063 by using the disc diffusion and micro dilution methods. The inhibition activities of these compounds on carbonic anhydrase II enzyme (hCA II) have been investigated by comparing IC50 and K-i values. The anticancer activities of these compounds on MCF-7 cell line investigated by comparing IC50 values. The biological activity screening showed that Cu(II) complex has more activity than ligand against the tested bacteria, hCA II enzyme and breast cancer cell lines MCF-7. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Butane sulfonic acid hydrazide; Cu(II) complex; Biological activities; Electrochemical studies; Crystal structure; DFT